Semiotic Analysis and Moral Message in the Film Parasite - Andriani, Astri Dwi; Anggraeni, Yuni Sri (MultiTech Publisher, 2023)
The 2019 film Parasite is a film that tells about social and economic disparities in the lives of two families, which carries many moral messages for film lovers in Cianjur. The topic of Parasite 2019 is considered to attract the attention of researchers because the film was widely discussed and was a trend at that time, receiving many nominations and world awards. The 2019 film Parasite became the first film from South Korea to receive an Academy Award nomination and the first non-English language film to win a nomination for best film. The film also received four nominations at the 73rd British Academy Film Awards, winning for film not in the English language and best original screenplay. The film was also the first non-English language film to win the Screen Actors Guild Award for outstanding performance in a motion picture. This film by director Bon Joon Ho managed to get more than 10 million viewers, namely a total of around 10,249,000 viewers. This research is qualitative research using John Fiske's hermeneutics and semiotics approach. There are stages for analyzing objects according to John Fiske, namely the Reality and Representation stages. The results of this research show that the 2019 film Parasite is a film that represents the meaning of social and economic inequality that occurs in South Korea which is packaged nicely in a film